Bentuk dan Ruang Arsitektur Masjid Agung Demak - Anita Rahma Fauziah; Shofiya Intan Cahyani; Miftahul Khairi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The Great Mosque of Demak is one of the oldest mosques on the island of Java, this mosque was built in the 15th century AD, with a unique architectural style that reflects the acculturation of Hindu-Javanese culture in harmony with Islamic principles. In writing this article, the author uses a qualitative approach method with a descriptive method. This approach was chosen to deeply understand the phenomenon of the form and space of the architecture of the Great Mosque of Demak through direct observation and data analysis. The acculturation of Hindu-Buddhist culture seen in the Great Mosque of Demak is found in the use of the tumpeng concept on its roof which is similar to the shape of a Hindu-Buddhist temple and also the shape of the pillars and the structure of the room are inspired by the Hindu-Buddhist pendopo architecture. Acculturation of Javanese culture is also applied to its roof which is in the form of a three-tiered pyramid, the use of wood as a building material, four main pillars (Saka Guru), Bulus ornaments, and Tajug typology. The Great Mosque of Demak is one of the most prominent examples of cultural and architectural acculturation in Indonesia. This mosque has succeeded in uniting local Javanese elements with Islamic traditions, creating a unique and meaningful building.